2019
DOI: 10.1055/s-0039-1683354
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Fertilization and Vasa Previa: A Report of Two Cases

Abstract: Vasa previa (VP) is a dangerous obstetric condition associated with perinatal mortality and morbidity. In vitro fertilization (IVF) is a risk factor for VP due to the high incidence of abnormal placentation. The diagnosis should be made prenatally, because fetal mortality can be extremely high. We report two cases to demonstrate the accuracy of transvaginal ultrasound in the prenatal diagnosis of VP. A 40-year-old primiparous Caucasian woman with IVF pregnancy was diagnosed with VP at 29 weeks of gestation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 13 publications
2
8
0
Order By: Relevance
“…An association of vasa previa with IVF pregnancies was also reported by Oyelese et al and Isotton et al 156 , 157 …”
Section: Structural Abnormalities Of the Umbilical Cordsupporting
confidence: 66%
See 1 more Smart Citation
“…An association of vasa previa with IVF pregnancies was also reported by Oyelese et al and Isotton et al 156 , 157 …”
Section: Structural Abnormalities Of the Umbilical Cordsupporting
confidence: 66%
“…154 In a review study, Jauniaux et al confirmed that the incidence of twin gestations diagnosed with vasa previa in cohort and case-control studies was 11% and concluded that there is sufficient evidence to warrant guidelines for targeted screening. 155 An association of vasa previa with IVF pregnancies was also reported by Oyelese et al and Isotton et al 156,157 Marginal Insertion of the Umbilical Cord Of note, it appears that attention should also be directed at sonographic depiction of marginal umbilical cord insertion (Figures 4 and 5) in that this condition has been associated with an increase in both adverse maternal and perinatal outcomes. 106,158…”
Section: Dovepresssupporting
confidence: 53%
“…Animal model studies have revealed that repetitive UC compression disturbs the fetal acid-base status and can ultimately result in cardiovascular collapse [39,40]. These studies clearly indicate that UCA is the cause of stillbirth.…”
Section: Marseille May 17 1960mentioning
confidence: 94%
“…Pregnant women must always be informed of these findings by the obstetrician and/or nurse-midwife. The possibility of stillbirth far outweighs any concerns regarding maternal anxiety [39,40].…”
Section: Marseille May 17 1960mentioning
confidence: 99%
“…PPP refers to the placenta attached to the scar of the previous cesarean section, or the placenta previa with placenta accreta or placental adhesions. Relevant data show that the risk of placental implantation is 50 %, which may lead to intraoperative and postoperative bleeding that is difficult to control during cesarean section, which may cause hemorrhagic shock and diffuse intravascular coagulation, endangering the life of the mother and increase perinatal hysterectomy rate [3][4][5] . With the opening of the two-child policy, it is foreseeable that the cesarean section rate, which was as high as 50 % in China, will cause a huge number of PPP parturients, and how to deal with the intraoperative bleeding is one of the most pressing problems for obstetricians in China [6,7] .…”
mentioning
confidence: 99%